2020
DOI: 10.1016/j.ejro.2020.100306
|View full text |Cite
|
Sign up to set email alerts
|

Non-contrast versus contrast-enhanced MR in the diagnosis of spondylitis: A quantitative concordance-analysis

Abstract: Introduction : Magnetic Resonance (MR) imaging using gadolinium contrast media is an essential imaging modality in diagnosing spondylitis. However, gadolinium contrast is not widely available in Indonesia and relatively expensive. Many MR studies in Indonesia are performed without contrast administration. It is unclear how confident non-contrast MR can diagnose tuberculous spondylitis in comparison to standard contrast MR. Purposes : This study aims to evaluate the conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…This is in line with previous research which found that all research samples experienced endplate disruption. This endplate disruption occurs in the initial phase of the formation of intervertebral disc destruction in the anterior part due to infection which will continue to spread to the lower area to the intervertebral disc (10). This study also showed that all tuberculous spondylitis patients experienced paravertebral abscesses (100%).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…This is in line with previous research which found that all research samples experienced endplate disruption. This endplate disruption occurs in the initial phase of the formation of intervertebral disc destruction in the anterior part due to infection which will continue to spread to the lower area to the intervertebral disc (10). This study also showed that all tuberculous spondylitis patients experienced paravertebral abscesses (100%).…”
Section: Discussionmentioning
confidence: 56%
“…MRI without contrast enhancement can show several observable features including corpus vertebra damage with spinal cord edema, endplate defects, paravertebral and epidural thickening. However, for determining the extent, size and extent of the abscess, it is superior to MRI with contrast enhancement which makes the application of contrast unavoidable for assessing further complications of spondylitis (10).…”
Section: Discussionmentioning
confidence: 99%
“…MRI plays an important role in the diagnosis of spinal TB in pregnancy. A recent study showed that there was no significant difference between the contrast and non-contrast MRI in diagnosing Pott disease, and concluded that both techniques were equally effective [ 17 ]. In our study, we used post-gadolinium contrast T1-weighted imaging.…”
Section: Discussionmentioning
confidence: 99%
“…In spine MRI, contrast-enhanced sequences are better in differentiating epidural fibrosis from disc herniation [ 105 ] and for characterisation of vertebral marrow infiltrative lesions [ 106 ]. The added value of GBCA is controversial for the diagnosis of spondylitis and its complications [ 107 ].…”
Section: Measures To Reduce Gbcamentioning
confidence: 99%